The psychopharmacology treatment planner - Purselle, David C. (J. Wiley & Sons, 2003)
The Psychopharmacology Treatment Planner provides all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payors, and state and federal review agencies